Development of chitosan/gelatin/keratin composite containing hydrocortisone sodium succinate as a buccal mucoadhesive patch to treat desquamative gingivitis - Davoudi, Zahra; Rabiee, Mohammad; Houshmand, Behzad; Eslahi, Niloofar; Khoshroo, Kimia; Rasoulianboroujeni, Morteza; Tahriri, Mohammadreza; Tayebi, Lobat (Drug development and industrial pharmacy, 2018)
The aim of this research was to develop chitosan/gelatin/keratin composite containing hydrocortisone sodium succinate as a buccal mucoadhesive patch to treat desquamative gingivitis, which was fabricated through an environmental friendly process. Mucoadhesive films increase the advantage of higher efficiency and drug localization in the affected region. In this research, mucoadhesive films, for the release of hydrocortisone sodium succinate, were prepared using different ratios of chitosan, gelatin and keratin. In the first step, chitosan and gelatin proportions were optimized after evaluating the mechanical properties, swelling capacity, water uptake, stability, and biodegradation of the films. Then, keratin was added at different percentages to the optimum composite of chitosan and gelatin together with the drug. The results of surface pH showed that none of the samples were harmful to the buccal cavity. FTIR analysis confirmed the influence of keratin on the structure of the composite. The presence of a higher amount of keratin in the composite films resulted in high mechanical, mucoadhesive properties and stability, low water uptake and biodegradation in phosphate buffer saline (pH = 7.4) containing 10 4 U/ml lysozyme. The release profile of the films ascertained that keratin is a rate controller in the release of the hydrocortisone sodium succinate. Finally, chitosan/gelatin/keratin composite containing hydrocortisone sodium succinate can be employed in dental applications.